The eye of the wolf - Sahana Baliga; Samyak Mulkutkar; C Balakrishnan (Indian Journal of Rheumatology)
Systemic lupus erythematosus is a chronic multisystemic disease with ocular manifestations seen in up to 90% of patients during their disease course. Ophthalmic manifestations can be due to disease activity or complications of therapy. Detailed history and careful examination are essential to differentiate between the entities. Timely accurate diagnosis and prompt treatment can save vision. We report two patients, one with lupus activity and the other with ocular infection to bring out the nuances in the management of such patients.